2020
DOI: 10.1111/febs.15637
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted role of TRAIL signaling in cancer and immunity

Abstract: 2 Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) is a member of the TNF 3 superfamily that can lead to the induction of apoptosis in tumor or infected cells. However, activation 4 of TRAIL signaling may also trigger non-apoptotic pathways in cancer and in non-transformed cells, 5 i.e. immune cells. Here, we review the current knowledge on non-canonical TRAIL signaling. The 6 biological outcomes of TRAIL signaling in immune and malignant cells is presented and explained, 7 with a focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 255 publications
(300 reference statements)
2
52
0
Order By: Relevance
“…TNFRSF6B itself can attenuate inflammation and overexpression of this proteins has been related to breast cancer progression ( 37 , 38 ). TNFSF10 is another ligand with both pro- and anti-apoptotic effects as well as effects on the immune response ( 39 ). These data have been corroborated by genome wide screens that recently uncovered the TNF-pathway as essential for susceptibility of immunotherapy and important for the understanding of the immune response in cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNFRSF6B itself can attenuate inflammation and overexpression of this proteins has been related to breast cancer progression ( 37 , 38 ). TNFSF10 is another ligand with both pro- and anti-apoptotic effects as well as effects on the immune response ( 39 ). These data have been corroborated by genome wide screens that recently uncovered the TNF-pathway as essential for susceptibility of immunotherapy and important for the understanding of the immune response in cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-related apoptosis induced ligand (TRAIL) is a homotrimeric protein that its main role is for modulating immune responses ( 88 ). Expression of TRAIL on T and NK cells is important for controlling tumor immune surveillance ( 89 ). TRAIL type 2 receptor (TRAIL-R2) (also called death receptor 5/DR5) is a membrane-bound death receptor ( 90 ) that is expressed mainly on endothelial cells (ECs) and immune cells ( 88 ).…”
Section: Factors Related To the Differentiated Cellular State In Tumor Immune Ecosystemmentioning
confidence: 99%
“…Activation of proinflammatory pathways by TRAIL increases proliferation, migration, invasion and/or metastasis of cancer cells, primarily through nuclear factor-kappa B (NF-κB), PI3K, AKT and MAPK [ 10 , 11 , 12 ]. Recent studies have confirmed that NF-κB is often constitutively activated in human cancer cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%